Fabrication of SWCNT/TiO2 for Creating Self-Cleaning Property on the Glass - khalaji assadi, morteza (2016)
The significance of this research is to fabricate a Single Wall Carbon Nanotubes/ Titanium dioxide (SWCNT/TiO2) composite to be coated on glass which has the self-cleaning property. It has been observed that the surface of the glass tends to get dirty and dusty with time. The objectives of this paper are to compare and analyze the transmittance and also the photocatalytic activity of the nanocomposite solutions prepared. The method used to fabricate this composite is sol-gel synthesis as it has a higher amount of dispersion and is the easiest way to use and the method used to coat the solution on substrate is spin coating method since it has a uniform coating compared to other methods. It is important to ensure that the solution prepared is transparent so as to ease the coating process. 20 different samples were fabricated using different amount of SWCNT and TiO2 composition. In order to analyze transparency and photocatalytic activity, two different characterizations were conducted namely Fourier Transform Infrared Radiation spectroscopy (FTIR) for transmittance and Ultraviolet Visible absorption spectroscopy (UV-vis) for Methylene Blue (MB) concentration photodegradation. The highest transmittance obtained were (a) 10ml of TiO2, 0.04g SWCNT which was 82.2% and (b) 10ml of TiO2, 0.06g SWCNT which was 73.2% of transmittance. Also, the lowest concentrations achieved by MB are (a) 10ml of TiO2, 0.06g SWCNT which was 2.48mg/L and (b) 7.5ml TiO2, 0.02g SWCNT which was 3.1mg/L. By comparing the transmittance and photocatalytic activity, the highest efficiency obtained were (a) 10ml TiO2, 0.06g SWCNT which was 64.6% and also (b) 7.5ml TiO2, 0.04g SWCNT which was 56.3%.